Introduction Of New Student Admission Patterns Through Past Learning - Gianti, Ridhoul Wahidi; Murni, Dewi; Khairudin, Fiddian; Amaruddin, Amaruddin; Nasrullah, Nasrullah; Syafril, Syafril; Maimunah, Maimunah (CV. Pustaka An Nur, 2025)
The introduction of New Student Admission Patterns (PMB) through Past Learning (RPL) is an innovative approach in the higher education system to improve the quality of student admissions. RPL recognizes the experience and knowledge gained from non-formal and informal education, thereby providing opportunities for individuals with diverse backgrounds to continue their studies. This activity was carried out by the Socialization Team of the Faculty of Islamic Sciences, Indragiri Islamic University (UNISI). The socialization was carried out at PP Nur Darissalam, Kempas District, Indragiri Hilir Regency. The methods used are presentations, interactive discussions, and question and answer sessions. This service aims to analyze the effectiveness of RPL in the PMB process, as well as its impact on student academic success. The methods used include socialization and analysis of student admissions data. The results show that implementing RPL can increase the accessibility of higher education and encourage diversity among new students. In addition, RPL contributes to the development of students' soft skills and learning readiness. This research provides recommendations for educational institutions in optimizing student admissions through RPL so that they can create an inclusive and competitive learning environment.